Efficacy of Warm Ginger Foot Soak on Gout Arthritis Pain in Lepasan Village - Dewi Nurhanifah; Hendry Wardhana; Renaldy Rahman; Krisneni Sibuea; Nabila Nabila (OMNICODE Journal (Omnicompetence Community Developement Journal), 2026)
Effective community health initiatives necessitate accessible complementary interventions for managing gout arthritis. This community service initiative aimed to educate residents and implement warm ginger foot soak therapy as a non-pharmacological pain management strategy. The intervention was implemented in Lepasan Village, Barito Kuala, involving 25 local participants. The protocol encompassed hyperuricemia screening, baseline pain assessment, health education, ginger decoction preparation, and a 15–20 minute foot soak at approximately 40°C, followed by post-intervention evaluation. The participant cohort predominantly comprised females aged 40 to 60 years. Initial baseline assessments indicated that most participants experienced moderate pain levels. Post-intervention analysis revealed notable pain reduction, with participants transitioning from severe to moderate, and moderate to mild pain categories. Consequently, warm ginger foot soak therapy serves as an effective, accessible complementary nursing intervention for mitigating gout-related joint pain and enhancing patient comfort in community settings.